Synthesis, Spectral Characterization and Crystal Structure of (E)-4- Hydroxy-N -(2-methoxybenzylidene) benzohydrazide - Rassem, Hesham H. A.; Nour, A. H. (AENSI Publishing, 2016)
A Schiff base, (E)-4-Hydroxy-N -(2-methoxybenzylidene) benzohydrazide, (E4HB) had been synthesized in good yield by the acid-catalyzed condensation methoxybenzaldehyde and 4-hydroxybenzhydrazide in synthesized compound was elucidated by elemental analysis (CHN), FTIR, 13C-NMR and single crystal X-ray diffraction. E4HB crystallized in the crystal system with space group Z = 8, V = 2656.74(10) Å3 14.3951(3) Å, b = 8.7449(2) Å, c =21.1047(4) Å . The crystal structure of the compound is stabilized by intermolecular N1—H1N1….O2, O1 C13—H13A…O1 hydrogen bonds. A π—π interaction with centroid of 3.628 (6) A also occurs (Cg1 = C9— C14, -x, -y, -z).